Analisis Protein, Kalsium dan Uji Organoleptik Biskuit Ikan Gabus (Channa striata) Sebagai Camilan Balita Stunting - Risma Apiyalita; Ika Amalina Bonita; Liyana Ilmiyati; Novia Rahmah Maulani Sahab (Universitas Muhammadiyah Semarang, 2026)
Stunting was a condition of failed child growth resulting in body length or height being smaller the child growth standard, namely with a body length for age or height for age index z-score below -2 (SD). This is due to nutritional deficiencies, namely protein and calcium. It was known that one of the treatments for stunting so far is snacks that are rich in nutritional content. Snakehead fish biscuits are expected to increase nutritional value, especially protein and calcium. Protein and calcium consumed together can increase child growth. Research Method was experimental with two repetitions, Completely Randomized Design (CRD) method with three treatment levels 75 g, 90 g, 105 g. Protein testing, namely kjeldahl, calcium using Atomic Absorption Spectrophometry (AAS), while organoleptics using the hedonic test. The average value protein content in F1 (9.95 g/100 g), F2 (10.15 g/100 g) and F3 (10.60 g/100 g). The average value calcium in F1 (87.50 mg/100 g), F2 (147.0 mg/100 g) and F3 (133.0 mg/100 g). The results statistical data analysis of ANOVA test showed differences between protein (p=0.012) and calcium (p=0.001), but there no difference between samples in the organoleptic test (p>0.05). The level panelist preference for aroma and taste parameters in F1 well as color and texture in F3. The results study showed the highest average value protein content in F3 (10.60) and calcium in F2 (147.0). The best formulation in F3 with the addition 105 g snakehead fish. Snakehead fish snacks are rich in protein (SNI 2973:2011) and Minister of Health Regulation Number 51 (2016), suitable as snacks for stunted toddlers..Keyword : biscuits snakehead fish, calcium, organoleptic, protein, stunting,